The Physiology Associated With “Bed Rest” and Inactivity and How It May Relate to the Veterinary Patient With Spinal Cord Injury and Physical Rehabilitation - Thomovsky, Stephanie A. (Frontiers in Veterinary Science, 2021)
Bed rest has been recognized as a treatment for various maladies since the time of Hippocrates. Up until the twentieth century it was commonly prescribed by human health care professionals as a treatment for a variety of ailments including spinal cord injury and disease. With time, the negative impact of bed rest was recognized as a source of slow and even reduced patient healing. As treatment paradigms shifted, the utility and importance of physical rehabilitation as a critical adjunctive treatment for human spinal cord patients became fully recognized. Today standardized physical rehabilitation protocols exist for humans with spinal cord disease, the same cannot be said for our veterinary patient with spinal cord injury. The purpose of this manuscript is to discuss the effects of inactivity on the musculoskeletal system and to explore how and why physical rehabilitation can play a critical role in improved mobility and overall health in the veterinary patient with spinal cord injury. Research with a focus on the effects of inactivity, in the form of cage rest, in the veterinary patient with spinal cord injury is lacking.